Albuminuria in Patients with Type 2 Diabetes Mellitus: a Single Center Cross-Sectional Study - Ghimire, Pukar; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Diabetes mellitus is one of the commonest non-communicable diseases in Nepal and is associated with long term microvascular and macro vascular complications. Detection of albumin in urine is the earliest recognizable feature in the development of proteinuric diabetic nephropathy. This study aims to study the prevalence as well the determinants of albuminuria in patient with Type 2 diabetes mellitus visiting the medical OPD of College of Medical Sciences-Teaching hospital. Methods: This was a cross-sectional study done from January to June 2022 among Type 2 diabetes patients presenting to medical OPD for the comprehensive diabetes management. Relevant epidemiological, clinical and laboratory data were obtained. Urine dipstick test was done to screen for albuminuria. The prevalence and determinants of albuminuria were studied. Results: Study among 360 patients with mean age of 58.5 + 10.9 years and the mean duration since the diagnosis of diabetes of 6.8 + 5.5 years, showed that the prevalence of albuminuria was 33.3%. Albuminuria in these patients was found to have significant association with age (P<0.001), duration since diagnosis of diabetes (<0.001) and HbA1c (P<0.001). No significant association of albuminuria was found with gender (P=0.087), hypertension (P=0.063) and previous use of Angiotensin-converting enzyme inhibitors/ Angiotensin II receptor blockers. (P=0.217) Conclusions: Albuminuria is highly prevalent among our cohort of diabetic patients. Increasing age, longer duration since diagnosis of diabetes and higher HbA1c are the factors significantly associated with it.